Associations between abdominal obesity and the risk of stroke in Chinese older patients with obstructive sleep apnea: Is there an obesity paradox? - Su, Xiaofeng; Li, Kailiang; Yang, Ling; Yang, Yang; Gao, Yinghui; Gao, Yan; Guo, JingJing; Lin, Junling; Chen, Kaibing; Han, Jiming; Liu, Lin (Frontiers in Aging Neuroscience, 2022)
ABSTRACT Background and purpose Abdominal obesity (AO) increases the risk of stroke and is common in Obstructive sleep apnea (OSA) patients, but AO’s relationship with stroke in elder patients with OSA is unclear. We investigated whether AO is a risk factor for stroke among Asian elder OSA patients. Methods In this combination of cross-sectional and longitudinal study, from January 2015 to October 2017, 1,290 elder patients (age ≥60 years) with OSA (apnea–hypopnea index ≥5 events/hour on polysomnography) were consecutively enrolled from sleep centers at six hospitals, evaluated for AO defined as waist circumference (WC) using standardized criteria for the Asian population, and followed up prospectively for median 42-month. Logistic regression and Cox analyses were used to determine the association between AO and stroke risk in these participants. Results Participants with AO had a higher prevalence of stroke at baseline.A higher incidence of stroke during a median 42-month follow-up than participants without AO (12.4% vs. 6.8% and 8.3% vs. 2.4%, respectively; both P<0.05). Cross-sectional analysis revealed an association between AO and stroke [odds ratio 1.96, 95% confidence interval (CI) 1.31–2.91], which was stronger among participants with moderate OSA (HR 2.16, 95% CI 1.05–4.43). Cox regression analysis showed that, compared to participants without AO, participants with AO had a higher cumulative incidence of stroke (HR 2.16, 95% CI 1.12–4.04) and the association of AO with severe OSA was stronger (HR 3.67, 95% CI 1.41–9.87) during a median 42-month follow-up. Conclusions The risk of stroke is associated with AO among the elder patients who has OSA , both at baseline and during follow-up, and the strength of the association varied by OSA severity. Active surveillance for early detection of AO could facilitate the implementation of stroke-preventive interventions in the Asian elder OSA population.